Work Values of Turkish and American University Students - Karakitapoğlu Aygün, Zahide (Journal of business ethics, 2008)
The first aim of this paper was to investigate how the traditional Protestant work ethic (PWE) and more contemporary work values (i.e., masculine, feminine, and entrepreneurship values) were related to one another, and differed across genders and two cultural contexts, namely Turkey and the U.S. The second aim was to elucidate the role of religiosity in PWE among the two cultural groups. Two hundred and sixty six American and 211 Turkish university students participated in this questionnaire study. The analyses examining cross-cultural differences revealed that Turkish university students reported greater scores in the PWE and all contemporary work values as compared to their American counterparts. For the Turkish sample, there were no gender-related differences in the PWE, whereas in the U.S. sample, men reported greater PWE scores than did women. With regard to gender differences in contemporary work values, our results showed that gender groups differed in feminine and entrepreneurship values in both cultural contexts; men emphasized femininity and entrepreneurship more than women in Turkey but the reverse was true in the U.S. Correlations between contemporary work values and the PWE illustrated that the PWE is associated with entrepreneurship and masculine values in both cultural contexts and with feminine values in the Turkish context. Finally, our results regarding the role of religiosity in PWE indicated that highly religious participants reported greater PWE scores than the less religious ones regardless of culture. Findings are discussed with reference both to differences in the two socio-cultural contexts and to recent change in the social structure of Turkish society.